(3JdNjU GdeaJGMs - (3GdbRhjfi eMeO Hf YHO GdQMef Hf YeQs; (3GdScGcj , SQGL GdOjf CHh jYbhH jhSa Hf CHj HcQ Hf eMeO Hf Ydj GdScGcj GdNhGQRej GdMfaj, GdScGcj,J (B626 (3g` s ((3YHO GdQMef ? s)
(3ChdgG (B:s
(3CeG HYO adeG cGf Yde GdHdGZI hcGf GdbSe GdKGef eaJGM GdYdhe GdPi Ufag s
(3BNQgG (B:s
(3HGdJCed eY GdJPcQ deGJbOe s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B222 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B282s
Keywords: (3GdHdGZIs